Mendedahkan Keberagamaan dalam Kebersamaan: Bentuk Pengejawantahan Spiritualitas Lokal Sedulur Sak Lawase di Kalasan - Johannes Setiawan; Masroer (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2022)
The research article entitled, "Exposing Religion in Togetherness: Forms of Embodiment of Local Spirituality of Sedulur Sak Lawase in Kalasan", was compiled with the intention of providing a comprehensive picture as well as analyzing it analytically with regard to the relationships of religious communities that are in an area that is unified in one cultural frame. Java as a local culture has a significant influence in the process of forming the current Indonesian national culture. By using a grounded research model and including methods, observation, interviews, FGDs and documentation, the results of this study indicate that the principle of Seduluran saklawase that lives in the (local) village community of Kalasan occurred through a socio-historical journey from generation to generation for centuries. Especially since the construction of Hindu and Buddhist temples in the Ancient Mataram period to the presence of Islam and Christianity. This then becomes the solid foundation of the values of togetherness and brotherhood (seduluran saklawase) which is practiced by the people of Kalasan village to this day so as to form deeply rooted spiritual values. The form of the principle of seduluran sak lawase is to instill a sense of brotherhood (kinship) that is spiritual in nature to anyone without discriminating against ethnicity, race, regional origin, even religion. The capital of togetherness then continues to experience re-contextualization according to the needs of the times, such as for the construction of public facilities (roads, sewers, patrol posts, and so on) and pays homage to the three sacred moments in the life of the Javanese, namely birth, marriage and death which are actually also a cycle, the basis of human life worldwide.